Copolymer for fabric treatment, fabric treating agent and application thereof
Through the copolymerization of silicon-modified perfluoropolyether acrylate and carbon-containing double-bonded capped isocyanate, the problem that existing waterproofing agents are difficult to achieve both hydrostatic pressure and waterproof and oilproof, and efficient waterproof and oilproof resistance are achieved, while avoiding the use of carcinogens.
Patent Information
- Application Number
- CN202010342269.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-04-27
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2040-04-27
AI Technical Summary
The existing fluorocarbon-based waterproof and oil-proofing agents are difficult to obtain both hydrostatic pressure resistance and waterproof and oil-proofing properties, and contain potential carcinogens. The use of perfluorooctanic acid and perfluorooctanane sulfonyl compounds is limited.
Silicon modified perfluoropolyether acrylate monomer and carbon-containing double bond blocked isocyanate monomer are used for copolymerization. Through the synergy between silicon modification and isocyanate, a copolymer with excellent waterproof and oil resistance and hydrostatic pressure resistance is formed.
It achieves efficient waterproof and oil-resistant properties and high hydrostatic pressure resistance, while avoiding the disadvantages of using potential carcinogens and perfluoroalkyl long-chain compounds.
Smart Images

Figure BDA0002468959610000111 
Figure BDA0002468959610000112 
Figure BDA0002468959610000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer materials, in particular to a copolymer for fabric treatment, and also to a fabric treatment agent containing the copolymer and application thereof. Background Art
[0002] The waterproof property of textiles is usually obtained by finishing with waterproofing agents. The waterproof finishing of textiles is to reduce the surface energy of the fabric by physical or chemical methods, so as to achieve the purpose of making the fabric surface less wetted by water molecules. Among the waterproof treatment agents commonly used in chemical methods, fluorocarbon compounds have the best waterproof effect. However, the monomers of fluorocarbon waterproof treatment agents, perfluorooctanoic acid (PFOA) and perfluorooctane sulfonyl compounds (PFOS), are potential carcinogens. During and after the finishing process, they will release toxic fluorides, which are harmful to the human body and the environment. On June 27, 2008, the European Union officially implemented the directive restricting the use of perfluorooctane sulfonyl compounds (PFOS), which will affect the export of textiles, leather, papermaking, packaging, printing and dyeing auxiliaries, cosmetics, etc. in my country. There are also many organizations in the world (such as the US Environmental Protection Agency, Canadian Environment Organization, etc.) that have standardized the production and use of perfluoro compounds. At present, some influential companies in the world, such as 3M, have stopped producing perfluoroalkyl long-chain compound products. Therefore, the research and development of perfluoroalkyl long-chain substitutes has attracted the attention of scientists. Finding alternatives to fluorine-containing treatment agents and adopting new finishing technologies are research hotspots in waterproof finishing.
[0003] In addition, the existing fluorocarbon water-based waterproof and oil-proof agents cannot have both hydrostatic pressure resistance and water and oil resistance. Generally, those with excellent hydrostatic pressure resistance can only have basic water resistance, and the oil resistance is not high. For example, the current hydrostatic pressure-resistant waterproof agent is generally polyurethane-type, which has low water and oil resistance.
[0004] However, the emergence of various functional clothing, such as protective clothing, medical fabrics, military clothing, etc., has put forward a demand for waterproofing agents that are both highly resistant to hydrostatic pressure and highly waterproof and oil-proof. The research and development of such waterproofing agents has become the current research trend of textile treatment agents. Summary of the invention
[0005] In order to solve the above technical problems, in the first aspect, the present invention provides a copolymer, which is prepared by polymerizing a silicon-modified perfluoropolyether acrylate monomer and a carbon-carbon double bond-terminated isocyanate monomer as raw materials;
[0006] The silicon-modified perfluoropolyether acrylate monomer is shown in formula (I):
[0007] AO-Rf-B-CH2-OM-Si-(N-CH=CH2)3 formula (Ⅰ)
[0008] In the formula (I), A is C substituted with one or more fluorine atoms. 1~16 Straight chain alkyl;
[0009] Rf stands for -(C4F8O) a -(C3F6O) b -(C2F4O) c -(CF2O) d -, wherein a, b, c and d each independently represent an integer from 0 to 200, and the sum of a, b, c, d is at least 1;
[0010] B is C substituted with 1 or more fluorine atoms 1~6 A straight alkylene chain;
[0011] M and N are independently selected from C 1~6 A straight alkylene chain or C 2~6 A branched alkylene chain;
[0012] The carbon-carbon double bond-containing blocked isocyanate monomer is prepared by reacting a blocking agent having an α-olefin bond with isocyanate.
[0013] Preferably, in the formula (I), A is C substituted with 3 to 7 fluorine atoms. 1~3 Straight chain alkyl; the sum of a, b, c and d is 1 to 40; B is C substituted with 2 to 6 fluorine atoms 1~3 A straight alkylene chain; M and N are independently selected from C 1~3 A straight alkylene chain.
[0014] Further preferably, in the copolymer, the silicon-modified perfluoropolyether acrylate monomer is selected from the following compounds:
[0015] CF3CF2CF2O-(C4F8O) 20 -(C3F6O) 20 -CF2CF2-CH2-O-CH2CH2-Si-(CH2CH2-CH=CH2)3
[0016] CF3O-(C4F8O) 10 -(C3F6O) 10 -(CF2O) 10 -CF2CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3
[0017] CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3
[0018] CF3CF2O-(C4F8O)20 -CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3
[0019] CF3CF2O-(C3F6O) 20 -CF2-CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3
[0020] CF3CF2CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3.
[0021] Preferably, the end-capping agent having an α-olefin bond is a terminal hydroxyl acrylate having an α-olefin bond.
[0022] The end-capping agent having an α-olefin bond is preferably one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate, or a combination of at least two thereof.
[0023] The isocyanate is a monoisocyanate, a diisocyanate or a polyisocyanate, preferably one or a combination of at least two of isocyanoethyl methacrylate, isocyanoethyl acrylate, toluene diisocyanate, diphenylmethane-4,4-diisocyanate, hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, xylylene diisocyanate, naphthalene-1,5-diisocyanate, cyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate and isophorone diisocyanate.
[0024] Further preferably, the carbon-carbon double bond-terminated isocyanate monomer is any one of hydroxyethyl methacrylate-terminated isocyanoethyl methacrylate, hydroxyethyl acrylate-terminated isocyanoethyl methacrylate, hydroxypropyl acrylate-terminated isocyanoethyl acrylate, hydroxyethyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated toluene diisocyanate, hydroxypropyl methacrylate-terminated tetramethylxylylene diisocyanate, hydroxyethyl acrylate-terminated tetramethylxylylene diisocyanate, hydroxypropyl methacrylate-terminated tetramethylxylylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated isophorone diisocyanate, hydroxypropyl methacrylate-terminated xylylene diisocyanate, and hydroxybutyl methacrylate-terminated hexamethylene diisocyanate, or a combination of at least two of them.
[0025] The present invention respectively uses hydroxypropyl methacrylate-terminated isophorone diisocyanate, hydroxypropyl methacrylate-terminated xylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxybutyl methacrylate-terminated hexamethylene diisocyanate, and hydroxyethyl methacrylate-terminated hexamethylene diisocyanate as carbon-carbon double bond-containing terminated isocyanate monomers for experiments, and obtains good waterproof and oil-proof and hydrostatic pressure resistance effects.
[0026] Preferably, the mass ratio of the silicon-modified perfluoropolyether acrylate monomer to the carbon-carbon double bond-terminated isocyanate monomer is (13-20):(5-8).
[0027] More preferably, the copolymer monomer raw material further contains: acrylate monomer and functional cross-linking monomer.
[0028] Further preferably, in the copolymer monomer raw material, the mass ratio of the silicon-modified perfluoropolyether acrylate monomer, the acrylate monomer, the carbon-carbon double bond-terminated isocyanate monomer and the functional cross-linking monomer is (13-20):(6-10):(5-8):(0.2-0.9); preferably, the mass ratio of the silicon-modified perfluoropolyether acrylate monomer, the acrylate monomer, the carbon-carbon double bond-terminated isocyanate monomer and the functional cross-linking monomer is (18-20):(6-7):(6-7):(0.2-0.6).
[0029] As a preferred embodiment, the acrylate monomer is arbitrarily selected from behenyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, n-hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, stearyl (meth)acrylate, methoxybutyl acrylate, 2-ethylbutyl acrylate, 1,3-dimethylbutyl acrylate, preferably dodecyl acrylate.
[0030] As a preferred embodiment, the functional cross-linking monomer is arbitrarily selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, glycidyl acrylate, glycidyl methacrylate, 3-chloro-2-hydroxypropyl methacrylate, vinylidene chloride, preferably glycidyl methacrylate.
[0031] As a preferred embodiment, the copolymer further comprises the following raw materials:
[0032] Emulsifiers, cosolvents, solvents and initiators.
[0033] Wherein, the emulsifier includes emulsifier A and emulsifier B; emulsifier A is a cationic surfactant, and emulsifier B is a non-ionic surfactant.
[0034] Emulsifier A is arbitrarily selected from at least one of cetyltrimethylammonium bromide, dodecylammonium chloride, cetylpyridinium bromide, dodecyltrimethylammonium acetate, tetradecyltrimethylammonium chloride, octadecyltrimethylammonium chloride, behenyltrimethylammonium chloride, dodecyltrimethylammonium chloride, behenyldimethylammonium chloride, dioctadecyldimethylammonium chloride, benzyldodecyldimethylammonium chloride, benzyltetradecyldimethylammonium chloride, and benzyloctadecyldimethylammonium chloride.
[0035] Emulsifier B is arbitrarily selected from at least one of sorbitan fatty acid esters, propylene glycol block polyethers, polyoxyethylene sorbitan fatty acid esters, fatty alcohol and ethylene oxide condensates, alkylphenol polyoxyethylene ethers, fatty acid polyoxyethylene esters, castor oil / hydrogenated castor oil and ethylene oxide condensates, propylene oxide condensates, and ethylene oxide condensates, wherein the sorbitan fatty acid ester is preferably sorbitan monolaurate, sorbitan monostearate, sorbitan monopalmitate, sorbitan monooleate, and sorbitan sesquistearate, and the polyoxyethylene sorbitan fatty acid ester is preferably polyoxyethylene sorbitan monostearate, polyoxyethylene sorbitan monooleate, polyoxyethylene sorbitan tristearate, and polyoxyethylene sorbitan monolaurate.
[0036] Preferably, the mass ratio of the cationic surfactant of emulsifier A to the nonionic surfactant of emulsifier B is (0.2-0.5):(1.5-2.4), preferably, the mass ratio of the cationic surfactant to the nonionic surfactant is (0.3-0.5):(1.6-2.2).
[0037] The emulsifier is preferably a combination of octadecyl trimethyl ammonium chloride, sorbitan fatty acid ester, propylene glycol block polyether and polyoxyethylene sorbitan fatty acid ester. Further preferably, the mass percentage contents of octadecyl trimethyl ammonium chloride, sorbitan fatty acid ester, propylene glycol block polyether and polyoxyethylene sorbitan fatty acid ester in the copolymer raw material (the copolymer raw material refers to all raw materials for the copolymerization reaction, including monomer raw materials, emulsifiers, initiators, solvents and co-solvents) are: 0.2-0.5%, 0.5-0.8%, 0.5-0.8%, 0.5-0.8%, and further preferably: 0.3-0.5%, 0.6-0.8%, 0.5-0.7%, and 0.5-0.7%, respectively.
[0038] The cosolvent is arbitrarily selected from dipropylene glycol, tripropylene glycol, acetone, ethanol, propanol, isopropanol, n-butanol, isobutanol, 3-methoxy-3-methyl-1-butanol, 2-tert-butoxyethanol, ethylene glycol, tetrapropylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, propylene glycol monomethyl ether, propylene glycol dibutyl ether, dipropylene glycol monomethyl ether, tripropylene glycol monomethyl ether, polyethylene glycol 200, polyethylene glycol 400, polyethylene glycol 800, preferably tripropylene glycol, and the mass percentage content in the copolymer raw material is preferably 4.5-5%.
[0039] The initiator is arbitrarily selected from ammonium persulfate, azobisisobutylamidine hydrochloride, potassium persulfate, preferably azobisisobutylamidine dihydrochloride, and the mass percentage content in the copolymer raw material is preferably 0.4-0.5%.
[0040] As a further preferred embodiment, the emulsifier is a combination of octadecyltrimethylammonium chloride, S-80 emulsifier, L-64 emulsifier and Tween-20 emulsifier.
[0041] In a second aspect, the present invention provides a method for preparing the copolymer, comprising mixing the monomer raw material with an emulsifier, a co-solvent and a solvent, heating to 50-60°C, stirring until the solid is dissolved, and then emulsifying and homogenizing to obtain a pre-emulsion; continuing to heat to 65-70°C, stirring evenly, and then adding an initiator and deionized water, and keeping the temperature to react for 5-10 hours.
[0042] In a third aspect, the present invention provides a fabric treating agent, comprising the copolymer or the copolymer prepared by the method. The fabric treating agent may also contain other acceptable ingredients of finishing agents on the basis of the copolymer.
[0043] In a fourth aspect, the present invention provides an application of the copolymer and a fabric treatment agent made from the copolymer in waterproofing, oil-proofing and hydrostatic pressure resistance treatment, preferably, application of the copolymer in waterproofing, oil-proofing and hydrostatic pressure resistance treatment of synthetic fabrics, non-woven fabrics, fiber products and cotton-containing products.
[0044] The copolymer for fabric treatment provided by the present invention adopts silicon-modified perfluoropolyether acrylate monomers instead of perfluoroalkyl acrylate monomers. On the one hand, a perfluoropolyether (PFPE) chain segment is introduced into the silicon-modified perfluoropolyether acrylate monomer. The perfluoropolyether is similar to perfluoroalkane and has higher thermal stability and oxidation stability than ordinary alkanes, good chemical inertness and insulation. In addition, since oxygen atoms are inserted into the perfluoropolyether chain segment and O (oxygen) atoms are contained between CC bonds, the perfluoropolyether does not have a dense fluorine shell like perfluoroalkane, small molecules can easily enter the main chain, the perfluoroether chain is easily degraded, has no bioaccumulation, and has no potential teratogenicity, carcinogenicity and other hazards to organisms. On the other hand, acrylate is modified with silicone. Silicone copolymer is a semi-organic high molecular polymer material. The main chain is composed of alternating silicon and oxygen atoms, and the side chain is an organic group, that is, non-polar organic groups are distributed on the periphery of the main chain of the silicone copolymer molecule, so it has excellent hydrophobicity. The silicone compound itself has very low solubility in water and is difficult to absorb water molecules. When they contact water droplets, the contact angle formed is large (>90°), so the water droplets cannot wet their surface. The Si-O bond energy in the silicone copolymer is 450kJ / mol, which is much larger than the CC bond energy of 351kJ / mol in the acrylic copolymer. In addition, the Si-O bond rotation barrier in silicone is low, the bond rotation is easy, the surface energy is small, and the molecular volume is large. By modifying acrylic resin with silicone, the low-temperature brittleness and high-temperature stickiness of acrylic ester are improved. After modification, it has the advantages of both, not only has super weather resistance, but also has excellent salt spray resistance, stain resistance, wash resistance and temperature change resistance, and the economic cost of silicone materials is relatively low.
[0045] In addition, the use of silicon-modified perfluoropolyether acrylate monomers also takes advantage of the low surface energy of fluorine. After the fabric is treated with it, the perfluorocarbon chains with extremely low surface energy stand upright on the surface of the copolymer molecules and extend outward like pig hair due to their strong rigidity and poor flexibility. In this way, when liquid drops onto the surface of the fabric, it is shielded by this layer of perfluorocarbon chains, exerting excellent waterproof and oil-proof effects. Therefore, the length and stacking state of the perfluorocarbon chains are the key to determining waterproof and oil-proof properties. In the prior art, fluorine-containing monomers and non-fluorine-containing monomers are generally copolymerized in a one-step process, but this often causes cross-stacked perfluorocarbon chains and non-fluorocarbon chains, and the waterproof and oil-proof properties of the fluorine-containing carbon chains cannot be fully exerted; the silicon-modified perfluoropolyether acrylate monomer used in the present invention uses a silicon-modified perfluoropolyether acrylate monomer containing multiple terminal double bonds. Due to its multiple polymerization sites, it produces a dendritic network molecular structure after reacting with acrylate, which is beneficial for the perfluoro side chain to be oriented outward and avoid cross-stacked perfluorocarbon chains. In this way, the fluorine atoms can achieve the maximum effective utilization rate, so that they can form a "shielding protection" for the main chain and internal molecules. The electron cloud of the fluorine atom shields the carbon-carbon main chain well, and the perfluoroalkyl group with low surface tension not only ensures the stability of the carbon-carbon bond, but also has an excellent waterproof and oil-proof effect.
[0046] In addition, the polysiloxane molecules in the silicone copolymer are in a helical structure, with the methyl groups arranged outward and rotating around the Si-O bond. The molecular molar volume is large, the cohesive energy density is low, and the surface tension is small, which makes the silicone resin have excellent waterproof properties; and the bond length of the Si-O bond in the silicone segment is greater than that of the CC bond, and there is a methyl shield, which makes the chain very soft. Since the fluorocarbon chain has low surface tension and the silicon oxygen main chain has the characteristics of soft curling, the introduction of silicon groups into the organic fluorine structure can also play the role of the fluorosilicone polymer interpenetrating network structure to show certain unique properties, and can improve the shortcomings of fluorosilicone materials such as poor adhesion, low hardness, general strength, and difficulty in curing at room temperature, so that the product can be more widely used and the performance can be mutually complementary and more perfect. They can not only play their respective advantages, but also have a good effect on the waterproof and oil-proof finishing of fabrics, and the fluorine content is low, saving costs. Therefore, fluorine-containing and silicon-containing monomers are inserted into the main chain of acrylic resin or grafted as side groups to generate a dendritic network structure, combining the advantages of silicone and organic fluorine compounds, thereby achieving excellent waterproof and oil-proof effects.
[0047] The invention adopts the emulsion with acrylate as the main raw material, so the emulsion has good light stability and weather resistance, excellent alkali resistance and chemical resistance, and strong bonding performance.
[0048] The copolymer for fabric treatment provided by the present invention adopts a carbon-carbon double bond-terminated isocyanate monomer, and the hydrostatic pressure resistance of the copolymer is improved by introducing a carbon-carbon double bond-terminated isocyanate, and synergistically with a fluorosilicone compound and a functional cross-linking monomer. Isocyanate itself cannot coexist in a solution containing active hydrogen and will be reacted, so that the -NCO bond is destroyed. However, after the -NCO bond is blocked by an acrylate containing an α-olefin bond, it can stably coexist with an aqueous resin containing active hydrogen at room temperature, and after film formation, it is thermally unblocked by heating, releasing free -NCO groups to participate in the cross-linking reaction with the active hydrogen on the fabric, and has the characteristics of storage stability and self-cross-linking film formation.
[0049] The copolymer for fabric treatment provided by the present invention has siloxane in the silicon-modified perfluoropolyether acrylate monomer that can be cross-linked with fabric, -NCO bond in the carbon-carbon double bond-terminated isocyanate monomer that can be cross-linked with fabric, and active functional groups in the functional cross-linking monomer that can be cross-linked with fabric, so that after heat treatment, the fabric treatment agent can form a dense and tight film on the fabric, and water cannot pass through the fabric under a large water pressure, achieving high hydrostatic pressure resistance. The copolymer for fabric treatment provided by the present invention utilizes the organic combination of fluorine-silicon structure and isocyanate to significantly improve the hydrostatic pressure resistance of the copolymer while ensuring good waterproof and oil-proof effects.
[0050] The copolymer for fabric treatment provided by the present invention has excellent waterproof and oil-proof performance and high-efficiency hydrostatic pressure resistance, and can meet the needs of various functional clothing, such as protective clothing, medical fabrics, military clothing, etc. The copolymer for fabric treatment provided by the present invention does not contain PFOA, PFOS, or perfluoroalkyl long chains, is an environmentally friendly treatment agent, is easily biodegradable, reduces biological toxicity, does not harm the human body, and is environmentally friendly; the fabric treated with the copolymer feels comfortable; therefore, the copolymer for fabric treatment provided by the present invention has a good industrial prospect. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is described in detail below.
[0052] In the present invention, methyl (meth)acrylate refers to methyl methacrylate and / or methyl acrylate. It can be inferred that other methyl groups in brackets have the same meaning. For example, butyl (meth)acrylate refers to butyl methacrylate and / or butyl acrylate.
[0053] The copolymer for fabric treatment provided by the present invention comprises the following comonomers:
[0054] (1) Silicon-modified perfluoropolyether acrylate monomer as shown in formula (I):
[0055] AO-Rf-B-CH2-OM-Si-(N-CH=CH2)3 Formula (I)
[0056] In the formula (I), A is C substituted with one or more fluorine atoms. 1~16 Straight chain alkyl;
[0057] Rf stands for -(C4F8O) a -(C3F6O) b -(C2F4O) c -(CF2O) d -, wherein a, b, c and d each independently represent an integer from 0 to 200, and the sum of a, b, c, d is at least 1;
[0058] B is C substituted with 1 or more fluorine atoms 1~6 A straight alkylene chain;
[0059] M and N are independently selected from C 1~6 A straight alkylene chain or C 2~6 A branched alkylene chain;
[0060] (2) Acrylate monomers;
[0061] (3) Carbon-carbon double bond-terminated isocyanate monomers;
[0062] (4) Functional cross-linking monomers.
[0063] For example, in the formula (I), A is C substituted with 3 to 7 fluorine atoms. 1~3 Straight chain alkyl; the sum of a, b, c and d is 1 to 40; B is C substituted with 2 to 6 fluorine atoms 1~3 A straight alkylene chain; M and N are independently selected from C 1~3 A straight alkylene chain;
[0064] Furthermore, the silicon-modified perfluoropolyether acrylate monomer may be a specific compound selected from the following:
[0065] CF3CF2CF2O-(C4F8O) 20 -(C3F6O) 20 -CF2CF2-CH2-O-CH2CH2-Si-(CH2CH2-CH=CH2)3
[0066] CF3O-(C4F8O) 10 -(C3F6O) 10 -(CF2O) 10 -CF2CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3
[0067] CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3
[0068] CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3
[0069] CF3CF2O-(C3F6O) 20 -CF2-CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3
[0070] CF3CF2CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3.
[0071] The preparation process of silicon-modified perfluoropolyether acrylate monomer is as follows:
[0072] The perfluoropolyether acyl fluoride is reacted with methanol to obtain perfluoropolyether methyl ester;
[0073] Perfluoropolyether methyl ester is hydrolyzed under the conditions of a basic catalyst and a solvent to obtain perfluoropolyether methanol;
[0074] The perfluoropolyether methanol is reacted with allyl bromide to obtain allyl perfluoropolyether;
[0075] Then, the allyl perfluoropolyether is subjected to a hydrosilylation reaction with trichlorosilane, wherein triacetoxymethylsilane is used as a dehydrating agent and platinum is used as a catalyst, and after the reaction is completed, a perfluoropolyether modified product having chlorosilane at the end is obtained;
[0076] Then the prepared modified product is reacted with allyl magnesium bromide to obtain silicon-modified perfluoropolyether acrylate monomer.
[0077] Take the following compound as an example:
[0078] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0079] The preparation process is:
[0080] (1) CF3CF2O-(C4F8O) 20 -CF2-CH2-OC(=O)F (Mw=5478g / mol) 300g and methanol 43.81g were stirred and reacted at room temperature for 24h, and the molar ratio of perfluoropolyether acyl fluoride to methanol was 1:25. After the reaction, the reaction mixture was placed in a separatory funnel, washed three times with methanol, and the lower layer sample was distilled under reduced pressure to obtain perfluoropolyether methyl ester;
[0081] (2) Add 100 g of perfluoropolyether methyl ester (Mw = 5490 g / mol) to a three-necked flask, add NaBH4 in three portions, a total of 6.89 g, the molar ratio of perfluoropolyether methyl ester to NaBH4 is 1:10, then add 200 mL of anhydrous ethanol, stir and react at room temperature under nitrogen protection for 24 h to obtain perfluoropolyether methanol;
[0082] (3) Under nitrogen protection, 50 g of perfluoropolyether methanol (Mw = 5462 g / mol) and 1.64 g of potassium tert-butoxide were added to a three-necked flask, and 75 mL of tert-butanol was added as a reaction solvent. Then, 1.33 g of allyl bromide was added dropwise. The molar ratio of perfluoropolyether methanol, potassium tert-butoxide and allyl bromide was 1:1.6:1.2. The reaction was carried out at 40°C for 6 h. After the reaction was completed, the reaction mixture was placed in a separatory funnel and washed with water. The lower layer sample was extracted with 200 mL of trifluorotrichloroethane. After the lower layer liquid was taken out and rotary evaporated, allyl perfluoropolyether was obtained:
[0083] CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2-CH=CH2;
[0084] (4) 20 g of the allyl perfluoropolyether obtained in step (3) and 20 g of 1,3-bis(trifluoromethyl)benzene, 0.06 g of triacetoxymethylsilane, and 1.36 g of trichlorosilane were mixed and stirred at 5°C for 30 min under a nitrogen atmosphere, and then 0.094 mL of a xylene solution containing 2% of a Pt complex of 1,3-divinyl-1,1,3,3-tetramethyldisiloxane was added, and then the temperature was raised to 60°C for reaction for 5 h. After the reaction was completed, the perfluoropolyether modified product with chlorosilane at the end was obtained by distillation under reduced pressure:
[0085] CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2-CH2-CH2SiCl3;
[0086] (5) 19 g of the perfluoropolyether modified product having chlorosilane at the end obtained in step (4) and 20 g of 1,3-bis(trifluoromethyl)benzene were stirred at 5° C. for 30 min under a nitrogen atmosphere, and then 26.4 mL of a 0.7 mol / L allyl magnesium bromide diethyl ether solution was added, stirred at room temperature for 10 h, and then cooled to 5° C., 5 mL of methanol was added, the temperature was raised to room temperature, filtered, and the volatile components were washed with methanol three times after reduced pressure distillation, and finally reduced pressure distillation was performed to obtain a non-volatile silicon-modified perfluoropolyether acrylate monomer:
[0087] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3.
[0088] Furthermore, the present invention provides a copolymer for fabric treatment, wherein the copolymer comprises raw materials in the mass percentage content shown in Table 1.
[0089] Table 1 Copolymer raw material composition
[0090]
[0091] Preferably, the present invention further provides a copolymer for fabric treatment, wherein the copolymer comprises the raw materials in the mass percentage content shown in Table 2.
[0092] Table 2 Copolymer raw material composition
[0093]
[0094]
[0095] The present invention provides a copolymer for fabric treatment, and the preparation method comprises the following steps:
[0096] Weigh the raw materials silicon-modified perfluoropolyether acrylate, lauryl acrylate, carbon-carbon double bond-terminated isocyanate, glycidyl methacrylate, octadecyltrimethylammonium chloride, sorbitan fatty acid ester, propylene glycol block polyether, polyoxyethylene sorbitan fatty acid ester, tripropylene glycol, and deionized water into a four-necked flask, heat to 50-60° C., preferably 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0097] The pre-emulsion is further heated to 65-70° C., preferably 67° C., and stirred evenly. Then, azobisisobutylamidine dihydrochloride and deionized water are added, and the mixture is kept warm for 7 hours to obtain a copolymer.
[0098] The following embodiments are specifically provided to illustrate the technical solutions of the present invention in detail through description of the embodiments.
[0099] Example 1
[0100] The copolymer of this embodiment is made from the following raw materials:
[0101] Silicon modified perfluoropolyether acrylate monomer:
[0102] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0103] Lauryl acrylate;
[0104] Hydroxypropyl methacrylate terminated isophorone diisocyanate;
[0105] Glycidyl methacrylate;
[0106] Octadecyltrimethylammonium chloride;
[0107] S-80 emulsifier (chemical composition: sorbitan fatty acid ester);
[0108] L-64 emulsifier (chemical composition: propylene glycol block polyether);
[0109] Tween-20 emulsifier (Chinese name: polyoxyethylene (20) sorbitan monolaurate);
[0110] Tripropylene glycol.
[0111] A method for preparing the copolymer is provided, the steps comprising:
[0112] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxypropyl methacrylate-terminated isophorone diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0113] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0114] Example 2
[0115] The copolymer of this embodiment is made from the following raw materials:
[0116] Silicon modified perfluoropolyether acrylate monomer:
[0117] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0118] Lauryl acrylate;
[0119] Hydroxypropyl methacrylate blocked xylylene diisocyanate;
[0120] Glycidyl methacrylate;
[0121] Octadecyltrimethylammonium chloride;
[0122] S-80 emulsifier;
[0123] L-64 emulsifier;
[0124] Tween-20 emulsifier;
[0125] Tripropylene glycol.
[0126] A method for preparing the copolymer is provided, the steps comprising:
[0127] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxypropyl methacrylate-terminated xylylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0128] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0129] Example 3
[0130] The copolymer of this embodiment is made from the following raw materials:
[0131] Silicon modified perfluoropolyether acrylate monomer:
[0132] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0133] Lauryl acrylate;
[0134] Hydroxypropyl methacrylate blocked hexamethylene diisocyanate;
[0135] Glycidyl methacrylate;
[0136] Octadecyltrimethylammonium chloride;
[0137] S-80 emulsifier;
[0138] L-64 emulsifier;
[0139] Tween-20 emulsifier;
[0140] Tripropylene glycol.
[0141] A method for preparing the copolymer is provided, the steps comprising:
[0142] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0143] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0144] Example 4
[0145] The copolymer of this embodiment is made from the following raw materials:
[0146] Silicon modified perfluoropolyether acrylate monomer:
[0147] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0148] Lauryl acrylate;
[0149] Hydroxybutyl methacrylate blocked hexamethylene diisocyanate;
[0150] Glycidyl methacrylate;
[0151] Octadecyltrimethylammonium chloride;
[0152] S-80 emulsifier;
[0153] L-64 emulsifier;
[0154] Tween-20 emulsifier;
[0155] Tripropylene glycol.
[0156] A method for preparing the copolymer is provided, the steps comprising:
[0157] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxybutyl methacrylate-terminated hexamethylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0158] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0159] Example 5
[0160] The copolymer of this embodiment is made from the following raw materials:
[0161] Silicon modified perfluoropolyether acrylate monomer:
[0162] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0163] Lauryl acrylate;
[0164] Hydroxyethyl methacrylate blocked hexamethylene diisocyanate;
[0165] Glycidyl methacrylate;
[0166] Octadecyltrimethylammonium chloride;
[0167] S-80 emulsifier;
[0168] L-64 emulsifier;
[0169] Tween-20 emulsifier;
[0170] Tripropylene glycol.
[0171] A method for preparing the copolymer is provided, the steps comprising:
[0172] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxyethyl methacrylate-terminated hexamethylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0173] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0174] Example 6
[0175] The copolymer of this embodiment is made from the following raw materials:
[0176] Silicon modified perfluoropolyether acrylate monomer:
[0177] CF3CF2CF2O-(C4F8O) 20 -(C3F6O) 20 -CF2CF2-CH2-O-CH2CH2-Si-(CH2CH2-CH=CH2)3;
[0178] Lauryl acrylate;
[0179] Hydroxyethyl methacrylate blocked hexamethylene diisocyanate;
[0180] Glycidyl methacrylate;
[0181] Octadecyltrimethylammonium chloride;
[0182] S-80 emulsifier;
[0183] L-64 emulsifier;
[0184] Tween-20 emulsifier;
[0185] Tripropylene glycol.
[0186] A method for preparing the copolymer is provided, the steps comprising:
[0187] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 3.9 g of hydroxyethyl methacrylate-terminated hexamethylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0188] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0189] Comparative Example 1
[0190] The copolymer of this comparative example is made from the following raw materials:
[0191] Silicon modified perfluoropolyether acrylate monomer:
[0192] CF3CF2O-(C4F8O) 20 -CF2CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3;
[0193] Lauryl acrylate;
[0194] Glycidyl methacrylate;
[0195] Octadecyltrimethylammonium chloride;
[0196] S-80 emulsifier;
[0197] L-64 emulsifier;
[0198] Tween-20 emulsifier;
[0199] Tripropylene glycol.
[0200] A method for preparing the copolymer is provided, the steps comprising:
[0201] Weigh 11.4 g of the above-mentioned silicon-modified perfluoropolyether acrylate monomer, 3.9 g of lauryl acrylate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0202] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0203] Comparative Example 2
[0204] The copolymer of this comparative example is made from the following raw materials:
[0205] Perfluorooctylethyl methacrylate;
[0206] Lauryl acrylate;
[0207] Hydroxyethyl methacrylate blocked hexamethylene diisocyanate;
[0208] Glycidyl methacrylate;
[0209] Octadecyltrimethylammonium chloride;
[0210] S-80 emulsifier;
[0211] L-64 emulsifier;
[0212] Tween-20 emulsifier;
[0213] Tripropylene glycol.
[0214] A method for preparing the copolymer is provided, the steps comprising:
[0215] Weigh 11.4 g of perfluorooctylethyl methyl methacrylate, 3.9 g of dodecyl acrylate, 3.9 g of hydroxyethyl methacrylate-terminated hexamethylene diisocyanate, 0.3 g of glycidyl methacrylate, 0.24 g of octadecyltrimethylammonium chloride, 0.42 g of S-80 emulsifier, 0.42 g of L-64 emulsifier, 0.42 g of Tween-20 emulsifier, 2.76 g of tripropylene glycol and 36 g of deionized water in a four-necked flask, heat to 55° C., stir until the solid is dissolved, and emulsify and homogenize the dissolved solution to obtain a pre-emulsion;
[0216] The pre-emulsion was further heated to 67° C. and stirred evenly. Then, 0.24 g of azobisisobutylamidine dihydrochloride and deionized water were added. The mixture was kept warm for 7 hours to obtain a copolymer.
[0217] Test example
[0218] The copolymers prepared in the above examples and comparative examples were tested for their properties. The testing process and data are as follows.
[0219] 1. Fabric treatment
[0220] Fabric finishing process: The copolymers prepared in Examples 1-5 and Comparative Examples 1-2 were diluted with deionized water to a concentration of 10 g / L, and then cotton cloth was taken and immersed in the seven dilutions prepared; after immersion for 20 minutes, the cotton cloth was taken out and rolled once with a rolling mill, and the liquid carrying rate was 100%; after the two-immersion and two-rolling process, the cotton cloth was first baked at 80°C for 5 minutes and then baked at 170°C for 10 minutes. Then the performance test was carried out.
[0221] 2. Fabric performance test after treatment
[0222] The treated cotton cloth was subjected to the following performance tests:
[0223] (I) Waterproof performance test
[0224] The water resistance test method is to conduct a spray water test in accordance with AATCC-22. The water resistance level is used to indicate the spray resistance. The suffix "+" attached to the data means that the performance is slightly better than the level performance represented by the numerical value, and the suffix "-" means that the performance is slightly worse than the level performance represented by the numerical value. The evaluation criteria are shown in Table 3.
[0225] Table 3 Waterproof performance
[0226] grade Evaluation Criteria 1 The entire sprayed surface is wetted 2 Half of the sprayed surface is wetted 3 The sprayed surface is not wetted but has continuous water droplets 4 The sprayed surface is not wetted, with a small amount of water droplets 5 The sprayed surface is not wetted and has no water droplets
[0227] (II) Oil resistance test
[0228] Oil repellency test method: The oil repellency test is carried out according to AATCC-TM118. The corresponding grade of oil is dropped on the fabric and the penetration is observed within 30 seconds. The highest grade of oil that is not penetrated is the oil repellency grade of the treatment agent. The standard evaluation is shown in Table 4.
[0229] Table 4 Oil resistance grade
[0230] grade Evaluation Criteria 1 Medical lubricants 2 Mixed solution of 35 parts hexadecane and 65 parts medical lubricant 3 Hexadecane 4 Tetradecane 5 Dodecane 6 n-Decane 7 n-octane 8 n-Heptane
[0231] (III) Hydrostatic pressure resistance test
[0232] Test method for hydrostatic pressure resistance: According to GB / T 4744-2013, use a hydrostatic pressure tester with a pressure increase rate set to 6kPa / min±0.3kPa. The value when three drops of water seep out of the fabric is the hydrostatic pressure resistance value. See Table 5 for standard evaluation.
[0233] Table 5 Evaluation of hydrostatic pressure resistance and waterproof performance
[0234]
[0235]
[0236] (IV) Performance test results
[0237] The performance test data of the copolymers prepared in various embodiments and comparative examples are shown in Table 6 below.
[0238] Table 6 Copolymer performance test results
[0239] serial number Waterproof Oil resistance Hydrostatic pressure resistance Example 1 5 6 2 Example 2 5 6 2 Example 3 5 7 3 Example 4 5 7 3 Example 5 5 7 4 Example 6 5 7 4 Comparative Example 1 4 5 1 Comparative Example 2 4 5 0
[0240] It can be concluded from the data in Table 6 that the copolymer prepared by the present invention can be used as a fabric treatment agent, and its waterproof, oil-proof and hydrostatic pressure resistance properties can reach a higher level. Compared with Comparative Example 1 (no carbon-carbon double bond-terminated isocyanate is added) and Comparative Example 2 (silicon-modified perfluoropolyether acrylate monomer is replaced by perfluorooctylethyl methyl methacrylate), the waterproof and oil-proof properties are improved, especially the hydrostatic pressure resistance is significantly improved, with unexpected technical effects. The copolymer prepared by the present invention is an excellent product that can replace perfluoroalkyl chain waterproofing agents, and can be used for surface treatment of various fabric surface substrates including various pure cotton, non-pure cotton, synthetic fabrics and non-woven fabrics, etc., to obtain excellent waterproof, oil-proof and hydrostatic pressure resistance properties of fabrics.
Claims
1. A copolymer, characterized in that It is made by polymerizing silicon-modified perfluoropolyether acrylate monomer and carbon-carbon double bond-terminated isocyanate monomer. The silicon-modified perfluoropolyether acrylate monomer is shown in formula (I): AO-Rf-B-CH2-OM-Si-(N-CH=CH2)3 Formula (I) In the formula (I), A is C substituted with one or more fluorine atoms. 1~16 Straight chain alkyl; Rf stands for -(C4F8O) a -(C3F6O) b -(C2F4O) c -(CF2O) d -, wherein a, b, c and d each independently represent an integer from 0 to 200, and the sum of a, b, c, d is at least 1; B is C substituted with 1 or more fluorine atoms 1~6 A straight alkylene chain; M and N are independently selected from C 1~6 A straight alkylene chain or C 2~6 A branched alkylene chain; The carbon-carbon double bond-containing blocked isocyanate monomer is prepared by reacting a blocking agent having an α-olefin bond with isocyanate. The mass ratio of the silicon-modified perfluoropolyether acrylate monomer to the carbon-carbon double bond-terminated isocyanate monomer is (13-20): (5-8), The copolymer monomer raw material also contains: acrylate monomer and functional cross-linking monomer.
2. The copolymer according to claim 1, characterized in that In the formula (I), A is C substituted with 3 to 7 fluorine atoms. 1~3 Straight chain alkyl; the sum of a, b, c and d is 1 to 40; B is C substituted with 2 to 6 fluorine atoms 1~3 A straight alkylene chain; M and N are independently selected from C 1~3 A straight alkylene chain.
3. The copolymer according to claim 1, characterized in that The silicon-modified perfluoropolyether acrylate monomer is selected from the following compounds: <h2 style=";text-align:left;direction:ltr">CF3CF2CF2O-(C4F8O)<h2 style=";text-align:left;direction:ltr"> 20 <h2 style=";text-align:left;direction:ltr"> -(C3F6O)<h2 style=";text-align:left;direction:ltr"> 20 <h2 style=";text-align:left;direction:ltr"> -CF2CF2-CH2-O-CH2CH2-Si-(CH2CH2-CH=CH2)3 <h2 style=";text-align:left;direction:ltr">CF3O-(C4F8O)<h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> -(C3F6O)<h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> -(CF2O)<h2 style=";text-align:left;direction:ltr"> 10 <h2 style=";text-align:left;direction:ltr"> -CF2CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3 CF3CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3 <h2 style=";text-align:left;direction:ltr">CF3CF2O-(C4F8O)<h2 style=";text-align:left;direction:ltr"> 20 <h2 style=";text-align:left;direction:ltr"> -CF2-CH2-O-CH2CH2CH2-Si-(CH2-CH=CH2)3 <h2 style=";text-align:left;direction:ltr">CF3CF2O-(C3F6O)<h2 style=";text-align:left;direction:ltr"> 20 <h2 style=";text-align:left;direction:ltr"> -CF2-CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2)3 CF3CF2CF2O-(C4F8O) 20 -CF2-CH2-O-CH2CH2-Si-(CH2-CH=CH2) 3 。 4. The copolymer according to any one of claims 1 to 3, characterized in that The end-capping agent having an α-olefin bond is a terminal hydroxyl acrylate having an α-olefin bond; The isocyanate is monoisocyanate, diisocyanate or polyisocyanate.
5. The copolymer according to claim 4, characterized in that The end-capping agent having an α-olefin bond is one of hydroxyethyl acrylate, hydroxypropyl acrylate, hydroxyethyl methacrylate, hydroxypropyl methacrylate, hydroxybutyl acrylate, and hydroxybutyl methacrylate, or a combination of at least two thereof; The isocyanate is one of isocyanoethyl methacrylate, isocyanoethyl acrylate, toluene diisocyanate, diphenylmethane-4,4-diisocyanate, hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, xylylene diisocyanate, naphthalene-1,5-diisocyanate, cyclohexyl diisocyanate, dicyclohexylmethane diisocyanate, tetramethylxylylene diisocyanate, and isophorone diisocyanate, or a combination of at least two thereof.
6. The copolymer according to any one of claims 1 to 3, characterized in that The carbon-carbon double bond-terminated isocyanate monomer is any one of hydroxyethyl methacrylate-terminated isocyanoethyl methacrylate, hydroxyethyl acrylate-terminated isocyanoethyl methacrylate, hydroxypropyl acrylate-terminated isocyanoethyl acrylate, hydroxyethyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated toluene diisocyanate, hydroxyethyl acrylate-terminated tetramethylxylylene diisocyanate, hydroxypropyl methacrylate-terminated tetramethylxylylene diisocyanate, hydroxypropyl acrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated hexamethylene diisocyanate, hydroxypropyl methacrylate-terminated isophorone diisocyanate, hydroxypropyl methacrylate-terminated xylylene diisocyanate, and hydroxybutyl methacrylate-terminated hexamethylene diisocyanate, or a combination of at least two thereof.
7. The copolymer according to any one of claims 1 to 3, characterized in that The mass ratio of the silicon-modified perfluoropolyether acrylate monomer, acrylate monomer, carbon-carbon double bond-terminated isocyanate monomer, and functional cross-linking monomer in the monomer raw material is (13-20): (6-10): (5-8): (0.2-0.9).
8. The copolymer according to claim 7, characterized in that The mass ratio of the silicon-modified perfluoropolyether acrylate monomer, acrylate monomer, carbon-carbon double bond-terminated isocyanate monomer, and functional cross-linking monomer in the monomer raw material is (18-20): (6-7): (6-7): (0.2-0.6).
9. The copolymer according to claim 1, characterized in that The acrylate monomer is arbitrarily selected from behenyl (meth)acrylate, methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, n-hexyl (meth)acrylate, octyl (meth)acrylate, decyl (meth)acrylate, dodecyl (meth)acrylate, octadecyl (meth)acrylate, stearyl (meth)acrylate, methoxybutyl acrylate, 2-ethylbutyl acrylate, 1,3-dimethylbutyl acrylate; And / or, the functional cross-linking monomer is arbitrarily selected from hydroxyethyl acrylate, hydroxyethyl methacrylate, glycidyl acrylate, glycidyl methacrylate, 3-chloro-2-hydroxypropyl methacrylate, and vinylidene chloride.
10. The copolymer according to claim 9, characterized in that The acrylate monomer is lauryl acrylate; And / or, the functional cross-linking monomer is glycidyl methacrylate.
11. The method for preparing the copolymer according to any one of claims 1 to 10, characterized in that: The monomer raw material is mixed with an emulsifier, a co-solvent and a solvent, heated to 50-60° C., stirred until the solid is dissolved, and then emulsified and homogenized to obtain a pre-emulsion; the mixture is further heated to 65-70° C., stirred evenly, and then an initiator and deionized water are added, and the mixture is kept warm for reaction for 5-10 hours.
12. A fabric treating agent, characterized in that: A copolymer comprising any one of claims 1 to 10 or a copolymer prepared by the method of claim 11.
13. Use of the copolymer according to any one of claims 1 to 10 or the fabric treating agent according to claim 12 in waterproofing, oil-proofing and hydrostatic pressure resistance treatment.
14. The use according to claim 13, characterized in that The application is application in waterproofing, oil-proofing and hydrostatic pressure resistance treatment of synthetic fabrics, non-woven fabrics, fiber products and cotton-containing products.
Citation Information
Patent Citations
Fluorine-free waterproof agent, and preparation method and applications thereof
CN109988264A
Fluorosilicone graft copolymer, surface treating agent and application
CN110894267A